The Museum on TikTok. An analysis of user-generated audiovisual production - Raquel Martínez-Sanz; Luis Felipe Solano Santos (Historia y Comunicación Social)
This paper analyzes, from a multimodal approach, the audiovisual production (n=110) and the reactions (n=10,444) uploaded to TikTok by personals profiles and with the museums as the protagonist. The objective is to discover the image that users project of the institution. We start from the premise that the dialogue favored by social media is a reflection of the conception that they have of the museum, conveying in their comments the experiences lived and even the functions assigned to it. The data reveals a predisposition of young people towards free, participative proposals that result in them having a good time. Furthermore, we discover the support and suggestions of different influencer profiles and their community of followers for getting to know the museum.